La bacteriosis comén del frijol en Dakota del Norte - Venette, J.R.=700 1 Grafton, K.F.; Groá, R.S.; Lamppa, C.P.
Sumarios (Es, En)
Keywords: PHASEOLUS VULGARIS; BACTERIOSIS; ENFERMEDADES DE LAS PLANTAS; EUA